PENGARUH STRES KERJA DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN PT DIKA BAGIAN DIVISI TELEMARKETING NTB (NEW TO BANK) BANK BCA - Sarmadan Efendi Harahap; Yusuf Supardi (Journal of Research and Publication Innovation, 2025)
The Influence of Job Stress and Work Morale on the Performance of PT DIKA Employees, Telemarketing Division NTB (New to Bank) of Bank BCA. The research method uses quantitative methods with a total of 73 respondents at PT DIKA, Telemarketing Division NTB (New to Bank) of Bank BCA. Data collection techniques include: 1) Primary Data (Observation and Questionnaire). 2) Secondary Data (books, journals and articles). The data analysis technique is instrument testing (validity test and reliability test). Classic assumption test (normality test, multicollinearity test, and heteroscedasticity test). The hypothesis tests used are multiple linear regression, partial test, summation test, and coefficient of determination test (R2). The results of this research show that: 1) Job stress has a positive influence on employee performance, as evidenced by the calculated t value of 3.033 > t table 1.994 with the hypothesis regression line equation being 0.391 (X1). 2) Work Morale has a positive influence on Employee Performance as evidenced by the calculated t value of 5.505 > t table 1.994 with the hypothesis regression line equation being 0.534 (X2). 3) Work Stress and Work Morale have a positive effect on Employee Performance as evidenced by the calculated f value of 41.696 > f table 3.128 with an f significance of 0.000 < 0.05 and an R2 value of 0.544 or 54.4%.